ANALYZING THE IMPACT OF QUALITY CONTROL CIRCLE AND SEVEN TOOLS METHODS ON ENHANCING PRODUCTIVITY - P, Ramlah; Najamuddin, Maffud Nur; Serang, Serlin (Jurnal Apresiasi Ekonomi, 2024)
The primary objective of companies involved in the production process is profitability, achieved through optimizing labor, raw materials, and resources. This continual improvement results in a robust production system geared towards generating significant profits. A prevalent method for ongoing refinement is the application of Quality Control Circles (QCC). This research focuses on assessing productivity improvements in the K84 Line Steering Handle following the implementation of QCC methodologies. It aims to understand the factors affecting productivity and applies QCC techniques to enhance efficiency. The research reveals promising findings, indicating that QCC-driven enhancements have substantially reduced cycle times across workstations. This reduction directly contributes to increased production output for the K84 Line Steering Handle. The utilization of QCC methods has proven remarkably effective, elevating efficiency levels from 65% to an impressive 92% and concurrently reducing manpower requirements by 3. In summary, this research emphasizes the transformative impact of QCC practices on productivity, highlighting substantial gains in output efficiency and resource optimization for the K84 Line Steering Handle. The integration of QCC-driven improvements has proven instrumental in achieving these positive outcomes. Keywords: Quality Control Circle, Seven Tools and Productivity